Utility of evoked potentials during anterior cerebral artery and anterior communicating artery aneurysm clipping - Rabai, Ferenc; Dorey, Claire M.; Fox, W. Christopher; Fitzgerald, Krista M.; Seubert, Christoph N.; Robicsek, Steven A. (Clinical neurophysiology practice, 2022)
•For anterior cerebral artery aneurysm clipping dual SSEPs and tcMEPs enhance detection of lower extremity deficits.•Evoked potentials have limited utility in predicting upper extremity deficits related to subcortical ischemia.•Four-extremity dual-modality monitoring can also detect pathogenetic mechanisms that are remote from the surgical site. To investigate the optimal combination of somatosensory- and transcranial motor-evoked potential (SSEP/tcMEP) modalities and monitored extremities during clip reconstruction of aneurysms of the anterior cerebral artery (ACA) and its branches. A retrospective review of 104 cases of surgical clipping of ruptured and unruptured aneurysms was performed. SSEP/tcMEP changes and postoperative motor deficits (PMDs) were assessed from upper and lower extremities (UE/LE) to determine the diagnostic accuracy of each modality separately and in combination. PMDs were reported in 9 of 104 patients; 7 LE and 8 UE (3.6% of 415 extremities). Evoked potential (EP) monitoring failed to predict a PMD in 8 extremities (1.9%). Seven of 8 false negatives had subarachnoid hemorrhage. Sensitivity and specificity in LE were 50% and 97% for tcMEP, 71% and 98% for SSEP, and 83% and 98% for dual-monitoring of both tcMEP/SSEP. Sensitivity and specificity in UE were 38% and 99% for tcMEP, and 50% and 97% for tcMEP/SSEP, respectively. Combined tcMEP/SSEP is more accurate than single-modality monitoring for LE but is relatively insensitive for UE PMDs. During ACA aneurysm clipping, multiple factors may confound the ability of EP monitoring to predict PMDs, especially brachiofacial hemiparesis caused by perforator insufficiency.